The pathogenesis of Parkinson's disease - Morris, Huw R; Spillantini, Maria Grazia; Sue, Carolyn M; Williams-Gray, Caroline H (The Lancet (British edition), 2024)
Parkinson's disease is a progressive neurodegenerative condition associated with the deposition of aggregated α-synuclein. Insights into the pathogenesis of Parkinson's disease have been derived from genetics and molecular pathology. Biochemical studies, investigation of transplanted neurons in patients with Parkinson's disease, and cell and animal model studies suggest that abnormal aggregation of α-synuclein and spreading of pathology between the gut, brainstem, and higher brain regions probably underlie the development and progression of Parkinson's disease. At a cellular level, abnormal mitochondrial, lysosomal, and endosomal function can be identified in both monogenic and sporadic Parkinson's disease, suggesting multiple potential treatment approaches. Recent work has also highlighted maladaptive immune and inflammatory responses, possibly triggered in the gut, that accelerate the pathogenesis of Parkinson's disease. Although there are currently no disease-modifying treatments for Parkinson's disease, we now have a solid basis for the development of rational neuroprotective therapies that we hope will halt the progression of this disabling neurological condition.